Determinan Perilaku Merokok pada Remaja Menurut Teori Health Belief Model: Studi Literatur Tahun 2014-2025 - Diyah Nur Muizzah; Luqman Effendi (Jurnal Ventilator, 2025)
Smoking behavior among adolescents is a serious and growing public health problem. Data from the 2023 Indonesian Health Survey (SKI) shows that 7.4% of adolescents aged 10–18 years smoke. This literature review aims to determine the determinants of smoking behavior among adolescents based on the Health Belief Model (HBM) theory, with a focus on components such as perceived vulnerability, perceived seriousness, perceived benefits, perceived barriers, cues to action, and self-efficacy. Using a literature review approach, this study identified and analyzed several academic references such as journals, books, encyclopedias, and others that discuss topics related to the determinants that influence smoking behavior among adolescents based on the Health Belief Model (HBM). The analysis conducted indicates that there is a relationship between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, perceived self-efficacy, cues to action, and smoking behavior among adolescents. The conclusion of this study shows that in 9 studies that applied the Health Belief Model (HBM) theory in examining smoking behavior in adolescents, all major components of HBM were proven to have a significant relationship with this behavior. This study provides an important theoretical basis for the development of effective and sustainable health promotion programs in controlling smoking behavior among adolescents.